1999
DOI: 10.1161/01.hyp.34.4.902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on Serum Ionized and Cytosolic Free Calcium

Abstract: Abstract-Elevated cytosolic free calcium (Ca i ) and reciprocally reduced, extracellular ionized calcium (Ca-ion) levels are observed in both hypertension and non-insulin-dependent diabetes mellitus (NIDDM). Because the changes of vascular function and insulin sensitivity in these conditions resemble the changes associated with "normal" aging, we wondered to what extent similar alterations in calcium metabolism occur with aging per se in the absence of overt hypertension or diabetes. We therefore measured plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
1
15
0
6
Order By: Relevance
“…Increased [Ca 2+ ] i has been suggested to be a common denominator for the association between Type 2 diabetes, hypertension and obesity [8,29]. Indeed, elevated basal [Ca 2+ ] i levels as well as defective membrane transport kinetics of Ca 2+ have been reported in all cell types in subjects with hypertension as well as in those with diabetes, even in the absence of overt hypertension [8,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Increased [Ca 2+ ] i has been suggested to be a common denominator for the association between Type 2 diabetes, hypertension and obesity [8,29]. Indeed, elevated basal [Ca 2+ ] i levels as well as defective membrane transport kinetics of Ca 2+ have been reported in all cell types in subjects with hypertension as well as in those with diabetes, even in the absence of overt hypertension [8,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan Tabel 6, terlihat bahwa terdapat perbedaan yang signifikan antara kadar Na+ serum pada penderita hipertensi dengan subjek normotensi dimana rata-rata kadar Na+ serum pada hipertensi (146.6±1.8mmol/L) lebih tinggi dibandingkan dengan normotensi (144.3±2.7mmol/L). Hasil penelitian ini sesuai dengan penelitian Barbagallo et al (2000) yang menyebutkan bahwa kadar Na+ serum pada penderita hipertensi lebih tinggi dibandingkan normotensi (141.0±0.4 >140.8±0.4mmol/L). Menurut Kee (1996) dan Chris (2010), kadar Natrium dalam darah normalnya adalah 135-145 mmol/L, dan pada penelitian ini hasil rata-rata kadar Na+ pada serum melampaui batas normal kadar Na+ dalam darah yang ditetapkan.…”
Section: Perbandingan Kadar Na+ K+ Cl- Dan Kalsium Total Pada Pendunclassified
“…Hasil penelitian ini didukung dengan penelitian Barbagallo et al (2000) yang menyebutkan bahwa kadar K+ serum pada penderita hipertensi lebih rendah dibandingkan normotensi (4.1±0.06<4.5±0.07mmol/L). Menurut Sacher (2002), nilai rujukan kadar Kalium dalam darah normalnya adalah 3.5-5.3 mmol/L, dan pada penelitian ini hasil rata-rata kadar K+ baik pada serum penderita hipertensi maupun subjek normotensi masih terdapat diambang batas normal nilai rujukan.…”
Section: Perbandingan Kadar Na+ K+ Cl- Dan Kalsium Total Pada Pendunclassified
“…54,55 Anomalies in the physical characteristics of the cell membranes and in calcium ions transport systems have been implicated in the pathogenesis of arterial hypertension. 56 On reviewing the enormous body of research on this subject, Swales 57 observes that all the cellular anomalies reported probably occur secondary to changes in sodium transport, so in cases of arterial hypertension, an altered calcium metabolism is due to an increase in the sodium intake.…”
Section: C a L C I U Mmentioning
confidence: 99%